The General College Five-to-Ten-Year Follow-Up Study. Volume V., Number Two - Minnesota Univ., Minneapolis. General Coll.; Kingsley, G. Gordon; Minnesota Univ., Minneapolis. General Coll. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
An eight year followup study of 300 randomly selected newly-registered students at the General College of the University of Minnesota is presented. The aim of the study was to determine the worth to student and taxpayer of extending higher education to those of lower-than-average college abilities. Interviews concerning academic abilities, vocational interests, and attitudes were held with participants during their stay in school. Questionnaires were mailed to those who had left. Followup letters were sent in 1966 to all 300 original participants, of whom 194 returned the requested information. A descriptive profile of the General College student emerged. Motivation is a prime factor in the success or failure of the students, calling for continual reevaluation of the curriculum and instructional methods in order to meet student needs and interests. Students in the survey were almost equally divided among those who might be considered academic and vocational successes, and those whose goals apparently were initially too high for possible success. The author suggests that in addition to curriculum evaluation, the College staff undertake in the very near future a second long-term study of student accomplishment. (CJ)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Academic Aptitude; College Students; Higher Education; Research Projects; Student Motivation; College Freshmen; Followup Studies; Longitudinal Studies; Student Needs